Clinical and economic burden of bacteremia due to multidrug-resistant organisms in Korea: a prospective case control study. (December 2022) - Song, Kyoung-Ho; Kim, Chung-Jong; Choi, Nam-Kyong; Ahn, Jeonghoon; Choe, Pyoeng Gyun; Park, Wan Beom; Kim, Nam Joong; Choi, Hee Jung; Bae, Ji Yun; Kim, Eu Suk; Lee, Hyunju; Park, Jeong Su; et al.
Highlights: Bacteremia due to 5 kinds of MDRO occurred in 7979 patients and caused 3280 deaths. Bacteremia due to MDRO caused 294 505 002 in socioeconomic loss. Tremendous clinical and economic burden occurred with MDRO bacteraemia. ABSTRACT: Objectives: The socioeconomic and clinical burden of multidrug-resistant organisms (MDRO), including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), multidrug-resistant Acinetobacter baumannii (MRAB), multidrug-resistant Pseudomonas aeruginosa (MRPA), and carbapenem-resistant Enterobacteriaceae (CRE) have not yet been adequately addressed. Methods: We prospectively searched for MDRO bacteremia cases with matched controls from 10 hospitals across Korea during a 6-month period in 2017. Patients were classified into the MDRO, susceptible organism, and no-infection groups. The corresponding susceptible or no-infection controls had been selected according to predefined criteria. We collected clinical information and estimated the total additional medical cost due to MDRO infections using the multistate model. Results: During the 6-month period, a total of 486 MDRO bacteremia cases (260, 87, 18, 20, and 101 cases of MRSA, MRAB, MRPA, CRE, and VRE, respectively) were identified. The 90-d mortality rates were 30.4%, 63.2%, 16.7%, 55.0%, and 47.5%, respectively. The additional costs caused by bacteremia were 15 768, 35 682, 39 908, 72 051, and 33 662 per MDRO type, respectively. Based on these 6-month data, the estimated annual number of bacteremia cases due to these five MDRO in Korea were 7979 (4070, 1396, 218, 461, and 1834 cases, respectively). Overall, this caused an estimated 3280 (1237, 882, 36, 254, and 871, respectively) deaths and cost 294 505 002 (84 707 359, 74 387 364, 10 344 370, 45 850 215, and 79 215 694, respectively) (range 170, 627, 020–416, 094, 679) in socioeconomic loss. Conclusions: A tremendous clinical and economic burden is caused by MDRO bacteremia compared with antibiotic-susceptible and no-infection groups. Substantial investment and efforts by related government agencies and medical staffs are needed.